Clinical and Genetic Heterogeneity in a Cohort of Chinese Children With Dopa-Responsive Dystonia - Chen, Yan; Bao, Xinhua; Wen, Yongxin; Wang, Jiaping; Zhang, Qingping; Yan, Jiayou (Frontiers in Pediatrics, 2020)
Background The aim of this study was to investigate the genetic and clinical features of dopa-responsive dystonia (DRD) in China. Method Characteristics of gene mutations and clinical manifestations of 31 patients diagnosed with DRD were analysed retrospectively. Result From January 2000 to January 2019, 31 patients were diagnosed with DRD. Twenty (64.5%) were male, and 11 (35.5%) were female. Ten patients (32.3%) had classic DRD, 19 (61.3%) had DRD-plus, and 2 (6.4%) patients had mutations in the dopamine synthetic pathway (PTS gene mutation) without a typical phenotype (not DRD or DRD-plus). Twenty-eight (90.3%) patients underwent genetic testing. Homozygous or compound heterozygous TH gene mutations were found in 22 patients. GCH1 and PTS gene mutations were found in 2 patients. Heterozygous TH mutation and genetic testing were negative in 1 patient. They took different doses of L-dopa, ranging from 0.4 to 8.7 mg/kg/d. Patients with classic DRD responded well. In patients with DRD-plus, 94.7% (18/19) responded well with residual symptoms. One patient (5.3%) did not show any improvement. Conclusion DRD can be divided into classic DRD and DRD-plus. In this cohort, the most common pathogenic gene was TH. Fever was the important inducing factor of the disease. L-dopa has sustained and stable effects on patients with classic DRD. In patients with DRD-plus, treatment with L-dopa could ameliorate most of the symptoms.